2015
DOI: 10.11613/bm.2015.027
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of acute kidney injury biomarkers in pediatric cardiac surgery

Abstract: IntroductionAcute kidney injury (AKI) is significant problem in children with congenital heart disease (CHD) who undergo cardiac surgery. The economic impact of a biomarker-based diagnostic strategy for AKI in pediatric populations undergoing CHD surgery is unknown. The aim of this study was to perform the cost effectiveness analysis of using serum cystatin C (sCysC), urine neutrophil gelatinase-associated lipocalin (uNGAL) and urine liver fatty acid-binding protein (uL-FABP) for the diagnosis of AKI in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…52 Petrovic et al estimated the prevalence of CKD in CHD patients based on the calculation of eGFR by SCR. 53 Blood Urea Nitrogen (BUN)…”
Section: Serum Creatinine (Scr)mentioning
confidence: 99%
“…52 Petrovic et al estimated the prevalence of CKD in CHD patients based on the calculation of eGFR by SCR. 53 Blood Urea Nitrogen (BUN)…”
Section: Serum Creatinine (Scr)mentioning
confidence: 99%
“…With a decision‐analytic Markov model, Petrovic et al. suggested that urinary liver‐type FABP yields both higher effectiveness and lower cost than neutrophil gelatinase–associated lipocalin (NGAL) and serum cystatin C in diagnosing acute kidney injury in pediatric cardiac surgery . Using a similar model, Critselis and colleagues reached the conclusion that an annual CKD273 classifier–based approach is more effectively, albeit costlier, in screening chronic kidney disease progression in comparison with urinary albumin excretion test …”
Section: Discussionmentioning
confidence: 99%
“…However, increased serum concentration can help to find out clinical and paraclinical requirement of CHD children [19]. Similarly, Cystatin C and serum creatinine level is used to establish acute kidney injury in children with congenital heart disease [2]. Cystatin C is a better glomerular filtration rate marker than serum creatinine [20].…”
Section: Physiological Markersmentioning
confidence: 99%
“…Tetralogy of Fallot [1] is, neonatal lupus or congenital heart block a significant health problem whose pathogenesis is quite complex [2]. Similarly, end-stage heart failure and abnormalities of bicuspid aortic valve are also congenital [3] (Table 1).…”
Section: Introductionmentioning
confidence: 99%